2001
DOI: 10.1521/psyc.64.4.319.18602
|View full text |Cite
|
Sign up to set email alerts
|

The Contribution of Early Traumatic Events to Schizophrenia in Some Patients: A Traumagenic Neurodevelopmental Model

Abstract: The current diathesis-stress model of schizophrenia proposes that a genetic deficit creates a predisposing vulnerability in the form of oversenstivity to stress. This model positions all psychosocial events on the stress side of the diathesis-stress equation. As an example of hypotheses that emerge when consideration is given to repositioning adverse life events as potential contributors to the diathesis, this article examines one possible explanation for the high prevalence of child abuse found in adults diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
301
2
9

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 514 publications
(333 citation statements)
references
References 143 publications
21
301
2
9
Order By: Relevance
“…Discussion of childhood trauma is often neglected or even actively avoided by clinicians (Read et al 2001); yet this review indicates that this should be an important consideration to identify individuals at increased risk of poor functional outcome. Despite evidence that childhood trauma may be more common among women in these patient groups Bonoldi et al 2013;Etain et al 2013), men still report high rates of exposure to adverse childhood experiences and screening should be considered a priority for both sexes.…”
Section: Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Discussion of childhood trauma is often neglected or even actively avoided by clinicians (Read et al 2001); yet this review indicates that this should be an important consideration to identify individuals at increased risk of poor functional outcome. Despite evidence that childhood trauma may be more common among women in these patient groups Bonoldi et al 2013;Etain et al 2013), men still report high rates of exposure to adverse childhood experiences and screening should be considered a priority for both sexes.…”
Section: Assessmentmentioning
confidence: 99%
“…Childhood trauma can have a number of detrimental effects on the developing brain (Read et al 2001;Neigh et al 2009;Tyrka et al 2013). Volumetric reductions in the amygdala (Soloff et al 2008;Aas et al 2012a;Hoy et al 2012), hippocampus (Hoy et al 2012), ventrolateral prefrontal cortex (Morandotti et al 2013) and in total grey matter (Sheffield et al 2013) have been reported among patients with psychotic disorders and borderline personality disorder with a history of childhood trauma compared with those without such a history.…”
Section: Brain Developmentmentioning
confidence: 99%
“…This suggests that lower than normal maternal or environmental care may lead to reduced NMDA receptor expression, and possibly, in humans, to an increased risk for schizophrenia. In humans, physical and sexual abuse in childhood has been linked to an increased risk of schizophrenia (Read et al 2001). While there is not enough evidence at this point to determine whether adverse environmental experiences during development are associated with the development of impaired NMDA receptor expression and cognitive coordination in humans, we suggest that this may be as fruitful an area to explore as that of the behavior genetics of cognitive coordination in schizophrenia.…”
Section: R61 Onset Of Illnessmentioning
confidence: 87%
“…This is mere speculation at present; however, two types of data are consistent with it. First, there are excessively high rates of child abuse reported in the histories of psychiatric inpatients with hallucinations (regardless of whether the diagnosis is schizophrenia), and among patients with schizophrenia (Read et al 2001), suggesting the presence of strong, often dissociated affect states. Second, there is evidence from the rat literature that when early development takes place in a deprived environment, NMDA receptor expression and, presumably, the potential for appropriate coordinating activity is reduced (Liu et al 2000).…”
Section: R5 Can Reduced Cognitive Coordination Account For the Emergmentioning
confidence: 99%
“…They supposed that stress worsens symptoms and that the diathesis is associated with a heightened response to stressors which may have the augmenting effect of the HPA axis on dopamine synthesis and receptors that in turn may lead to abnormal dopamine receptor functioning. In this connection, Read et al (2001) developed "a traumagenic neurodevelopmental model" that proposes that together with a genetic deficit also early adverse life events create a predisposing vulnerability in the form of hypersensitivity to stress that leads to typical neuroanatomical, cognitive or symptomatic features of schizophrenia. Barker et al (2015) suggests that a pathway from childhood maltreatment to psychosis leads via HPA axis hyperactivation, reduced hippocampal BDNF and oxytocin levels, and NMDA hypoactivation by glutamate to decreased hippocampal volume and increased mesolimbic dopamine.…”
Section: Trauma and Dissociationmentioning
confidence: 99%